The Role of Museums and Institutions in Holocaust Remedies - Erez, Noya; Justus Liebig University Giessen (My University, 2024)
This article is an essay written in the course of the post-Holocaust Remedies-Summer School 2023 and deals with the unique role of museums in the context of looted art.
Keywords: ddc:340